Fe3S4 nanoparticles for arterial inflammation therapy: Integration of magnetic hyperthermia and photothermal treatment. (March 2020) - Liu, Junchao; Guo, Xin; Zhao, Zhen; Li, Bo; Qin, Jinbao; Peng, Zhiyou; He, Guanjie; Brett, Dan J.L.; Wang, Ruihua; Lu, Xinwu
Graphical abstract: The integration of photothermal therapy and magnetic hyperthermia based on Fe3 S4 NPs have good potential for arterial inflammation therapy. Highlights: Fe3 S4 nanoparticles have the property of high photothermal efficiency and good magnetothermal efficiency. Fe3 S4 nanoparticles exhibit superior biocompatibility even at relatively high concentrations, which makes good prerequisites for Magnetic Hyperthermia application in vivo . The combination of photothermal therapy and magnetic hyperthermia based on Fe3 S4 NPs can eliminate inflammatory macrophages effectively, thus providing a new therapeutic strategy for the treatment of atherosclerosis and vessels stenosis. Abstract: Photothermal therapy (PTT), based on nanoparticles, has been widely explored in the treatment of multiple diseases. However, limited by laser penetration ability, its treatment efficiency can be reduced when treating deep arterial inflammation, which is the major cause of atherosclerosis and vessels stenosis. Magnetic hyperthermia (MHT) has the outstanding tissue permeability, while its magnetothermal efficiency was relatively poor. In this study, Fe3 S4 nanoparticles (NPs) were synthesized and characterized, and its dual capacity to convert light and magnetic stimulation into heat was confirmed. The Fe3 S4 NPs also presented superior biocompatibility and great T2 weighted magnetic resonance imaging properties (52.8 mM −1 S −1 ). Besides, its excellent effect in ablating inflammatory macrophages combining PTT and MHT was verified in vitro . In vivo experiment on Apo E-/- mice models exhibited that PTT combined with MHT could effectively eliminate infiltrating inflammatory macrophages and further inhibit the formation of arterial stenosis. This study concludes that the integration of PTT and MHT based on Fe3 S4 NPs can serve as an effective therapeutic strategy for the treatment of atherosclerosis and vessels stenosis.